Cytogenetic, cross-mating and molecular evidence of four cytological races of Anopheles crawfordi (Diptera: Culicidae) in Thailand and Cambodia - Saeung A. (Elsevier Masson SAS, 2014)
Twenty-nine isolines of Anopheles crawfordi were established from wild-caught females collected from cow-baited traps in Thailand and Cambodia. Three types of X (X1, X2, X3) and four types of Y (Y1, Y2, Y3, and Y4) chromosomes were identified, according to differing amounts of extra heterochromatin. These sex chromosomes represent four metaphase karyotypes, i.e., Forms A (X1, X2, X3, Y1), B (X1, X2, X3, Y2), C (X2, Y3) and D (X2, Y4). Forms C and D are novel metaphase karyotypes confined to Thailand, whereas forms A and B appear to be common in both Thailand and Cambodia. Cross-mating experiments between the four karyotypic forms indicated genetic compatibility in yielding viable progenies and synaptic salivary gland polytene chromosomes. The results suggest that the forms are conspecific and A. crawfordi comprises four cytological races, which is further supported by very low intraspecific variation (mean genetic distance = 0.000-0.018) of the nucleo.